Impact of a Bedside Activity Device on the Functional Status of Hospitalized Older Adults: A Randomized Controlled Trial. Issue 3 (March 2023) - Monica Fan, Peijin Esther; Louis, Joshua Kenneth; Lim, Xin Yi Cindy; Subramaniam, Sarasuathi Gloria Encio; Seow, Jason Phil; Aloweni, Fazila; Rajasegeran, Darshini Devi; Hsiang, Cheng Chia; Thilarajah, Shamala; Agus, Nur Liyana; Ong, Hwee Kuan; Ang, Shin Yuh; et al.
ABSTRACT: Background: Older adults may have difficulty maintaining their functional capabilities during hospitalization. This pilot study aimed to investigate the impact of a bedside activity device on the functional status of hospitalized older adults. Methods: For this single-site randomized controlled trial, 48 participants were recruited between July 2019 and March 2021. Participants were randomized into one of two groups: the intervention group, which was given the use of a bedside activity device plus standard care, and the control group, which received standard care. Katz Index of Independence in Activities of Daily Living (Katz ADL) scores and Timed Up and Go (TUG) test times were used as indicators of functional status and were collected on admission (baseline) and at discharge. Mann-Whitney U and χ 2 tests were used to test for baseline similarities between groups. The Wilcoxon signed rank test was used to determine within-group pre–post changes in TUG and Katz ADL scores. The Mann-Whitney U test was used to determine between-group differences in TUG and Katz ADL change scores. Results: Within-group pre–post analysis showed significant increases in Katz ADL scores in the intervention group and no significant changes in the control group. TUG times decreased significantly in the intervention group and increased significantly in the control group. Between-group analyses showed significant differences in both TUG and Katz ADL change scores. Conclusion: The use of the bedside activity device in addition to standard care may prevent functional decline and increase independence in performing basic ADLs. Abstract : This pilot study evaluated the use of a device equipped with exergames—interactive video games that incorporate physical exercise—in preventing functional decline and increasing patients' independence in basic activities of daily living.